Development of compact power electronics inverter using gallium nitride (GaN) devices - Sinurat, Hendry Donald Hanesty (2015)
The world of electronics industry has been increasing rapidly and expanding widely in the past three decades. Its development from time to time has shown huge potential to bring electronics into a more advanced and sophisticated stage. There are many aspects to be explored and discovered in a deeper way to display the power of electronics behind its unrevealed mystery. Demand of more ‘technological’ and ‘suit-in-extreme-operation’ electronic devices is climbing up like never before. Numerous numbers of electrical drives and machines are designed and produced to run under certain high level of frequency and temperature. To be noted, not to forget on high power density conversion system that is required and essential in many applications of power electronics. Electronic devices nowadays are getting shrink in dimension, yet the performance is forced to be upgraded or at least could achieve its normal merit of operation. In electronics, as the power density goes to be more compact, the power converted is expected to be smaller in its mechanical geometry. Semiconductor is known as the root of power electronics development over the years. However, the capability of single substrate of semiconductor, such as Silicon, has recently met its empirical limits in temperature and power ratings wise. Introduction of Silicon Carbide (SiC) and Gallium Nitride (GaN) has created another platform for power converter to develop and answer the needs of today’s electronics. Given the wide band gap of these materials, both provides several points of advantages in comparison with traditional Silicon-based converter. Points of merit like high energy band gap and high thermal conductivity, leads the converter to be able to operate in super low switching period (high frequency) and lessen the switching loss, hence resulting a high efficiency in the output power and high power density at the load end. This project locked its objective to do characterization of GaN-based devices, observing the behavior of switching speed of GaN-based devices, as well as to develop and optimize the performance in high frequency condition as to verify its ability in generating high efficiency output power.